The activity and use of zinc in poultry diets. Issue 1 (1st March 2016) - Naz, S.; Idris, M.; Khalique, M.A.; Zia-Ur-Rahman,; Alhidary, I.A.; Abdelrahman, M.M.; Khan, R.U.; Chand, N.; Farooq, U.; Ahmad, S.
Abstract : Zinc (Zn) is an important nutrient in poultry and its deficiency has been linked with various disorders, in addition to depressed growth and performance. It is now recognised that Zn has a major role in antioxidation, growth and development, production, immunity and stress related issues. Supplementation of Zn can improve growth, augment immunity, enhance antioxidant capacity, increase endocrine secretion and interact with other minerals in the gut. In this review, some of the basic information regarding the importance and activity of Zn within the body and the addition of Zn in poultry diets is discussed.